Theory of Reasoned Action : Purchasing Behavior of Batik Jambi - Utami, Febby Nanda; Usmayanti, Vivi; Fahdillah, Yosi; Yossinomita, Yossinomita; Pasaribu, Johni Paul Karolus; Kartika, Yulia Dwi (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2023)
One uniqueness that can be identified as a historical heritage in Indonesia is Batik. Almost every region in Indonesia has its characteristics, including motifs, color patterns, and philosophical meanings. In Jambi, Batik is always worn on formal occasions and has even become the community's uniform at various events. On the other hand, in terms of sales, MSMEs must maintain their brand quality and compete competitively in the market. Therefore, this study investigates consumers' brand image, attitude, and intention to buy Batik and the decision of consumer behavior to buy Batik as an implementation of the Theory of Reasoned Action (TRA). One hundred eighty-eight participants from Jambi province participated in filling out this online questionnaire. Then, the data that has been collected is tested using PLS-SEM. The results showed that all elements of TRA had a positive effect on the buying behavior of Batik in Jambi.